Influence of ecological and climatic conditions on the spread of Borrelia burgdorferi in domestic dogs in Ukraine - Panteleienko, O. V.; Makovska, I. F.; Tsarenko, T. M. (Regulatory Mechanisms in Biosystems, 2022)
Lyme-borreliosis is a zoonotic, infectious disease that has a complex chain of transmission of the pathogen Borrelia burgdorferi sensu lato and includes the relationship between ixodid ticks, vertebrate hosts, humans and companion animals in the environment. The article shows general trends in the prevalence of canine Lyme-borreliosis in Ukraine depending on environmental, climatic and physiographic factors. The results of a comparative cartographic analysis of the prevalence of Lyme borreliosis among domestic dogs in Ukraine are presented by systematizing, mathematical and statistical processing of the data obtained by surveying veterinarians engaged in clinical veterinary practice. The paper includes generalized data on the clinical manifestations, methods of diagnosis and treatment of Lyme borreliosis in dogs. We determined the dependence of the prevalence of Lyme borreliosis in dogs on the types of physical and geographical territories – natural zones of Ukraine. Each of the natural zones differs in types of relief, climatic conditions, soil types, composition of fauna and flora, which affect the epizootic chain of Lyme disease. There is a clear correlation between the incidence of Lyme borreliosis in dogs and the types of natural areas. The highest incidence of Lyme borreliosis in dogs was observed in the forest-steppe zone and the zone of broad-leaved forests. A sharp decrease in the incidence of dogs was recorded in areas of mixed forests, the Ukrainian Carpathians and in the South of Ukraine in the steppe zone. The study also confirmed that the prevalence of Lyme disease among domestic dogs was influenced by the climatic factors, in particular: gross moisture of territories, average annual air temperature and soil temperature. In Ukraine, veterinarians in the vast majority of cases use serological diagnostic methods: immunochromatographic analysis, immunoenzymatic assay, and western blot, which are insufficient, since the presence of antibodies to the Lyme borreliosis pathogen is only a confirmation of the animal’s contact with the antigen and may not indicate the presence of the disease in the clinical form. The generalized data on the use of antimicrobial drugs in the treatment of Lyme borreliosis in dogs indicate the predominant use of tetracycline antibiotics and cephalosporins. The majority of veterinarians reported symptoms of Lyme arthritis, somewhat fewer reported Lyme nephritis, neuroborreliosis, Lyme carditis and in rare cases, veterinarians observed erythema at the site of tick bite. About half of the veterinarians in Ukraine observed an increase in the incidence of Lyme disease in dogs, indicating a probable deterioration of the epizootic and epidemiological situation regarding Lyme borreliosis, especially in areas with favourable conditions for the circulation of Lyme borreliosis pathogens in natural and urban ecotopes. The results substantiate the need for the further study of the circulation of Borrelia burgdorferi sensu lato and their ability to cause disease in humans and animals, as well as the need to implement the principles of the One Health concept for the control and management of Lyme borreliosis.